Nano-CT as tool for characterization of dental resin composites - Håvard J. Haugen; Saad B. Qasim; Jukka P. Matinlinna; Pekka Vallittu; Liebert Parreiras Nogueira (NATURE RESEARCH, 2022)
Technological advances have made it possible to examine dental resin composites using 3D nanometer resolution. This investigation aims to characterize existing dental nano-hybrid and micro-hybrid resin composites through comparing and contrasting nano-computed tomography (nano-CT) with micro-CT and high-resolution SEM images. Eight commercially available and widely used dental resin composites, 2 micro-hybrid and 6 nano-hybrid were researched. Cured samples were examined and characterized using nano-CT (resolution 450 nm) and compared with micro-CT images (resolution 2 mu m). Acquired images were reconstructed and image analysis was carried out to determine porosity and pore morphology. A comprehensive comparison of scanning micrograph images unsurprisingly revealed that the nano-CT images displayed greater detail of the ultrastructure of cured dental resin composites. Filler particle diameters and its volumes were lower when measured using nano-CT, porosity being higher where analysed at higher resolution. There were large variations between the examined materials. Fewer voids were found in Tetric EvoCeram and IPS Empress Direct, the smallest pores being found in Universal XTE and Tetric EvoCeram. Nano-CT was successfully used to investigate the morphology of dental resin composites and showed that micro-CT gives a lower porosity and pore size but overestimates filler particle size. There were large discrepancies between the tested composites. Evidence of porosities and pores within a specimen is a critical finding and it might have a detrimental effect on a material's clinical performance.